On a putative type specimen of Pleurodema bibroni Tschudi, 1838 from Chile (Anura: Leptodactylidae) - Ferraro, Daiana Paola (2015)
The original description of the Neotropical frog Pleurodema bibroni was based on material collected at “Monte-Video” [Montevideo, Uruguay], but no type specimen was originally designated. In several publications, a specimen deposited at the National Museum of Natural History of Leiden (The Netherlands, RMNH 2277) and collected at Valparaíso, Chile, has been referred as type specimen of P. bibroni. Herein, it is argued that RMNH 2277 is not a type specimen of P. bibroni; nor can it be assigned to P. bibroni, but probably to Pleurodema thaul, a species with which P. bibroni was long confused.